Melatonin Attenuates Potato Late Blight by Disrupting Cell Growth, Stress Tolerance, Fungicide Susceptibility and Homeostasis of Gene Expression in Phytophthora infestans - Zhang, Shumin; Zheng, Xianzhe; Reiter, Russel J.; Feng, Shun; Wang, Ying; Liu, Sen; Jin, Liang; Li, Zhengguo; Datla, Raju; Ren, Maozhi (Frontiers in Plant Science, 2017)
Phytophthora infestans (P. infestans) is the causal agent of potato late blight, which caused the devastating Irish Potato Famine during 1845-1852. Until now, potato late blight is still the most serious threat to potato growth and has caused significant economic losses worldwide. Melatonin can induce plant innate immunity against pathogen infection, but the direct effects of melatonin on plant pathogens are poorly understood. In this study, we investigated the direct effects of melatonin on P. infestans. Exogenous melatonin significantly attenuated the potato late blight by inhibiting mycelial growth, changing cell ultrastructure, and reducing stress tolerance of P. infestans. Notably, synergistic anti-fungal effects of melatonin with fungicides on P. infestans suggest that melatonin could reduce the dose levels and enhance the efficacy of fungicide against potato late blight. A transcriptome analysis was carried out to mine downstream genes whose expression levels are affected by melatonin. The analysis of the transcriptome suggests that 66 differentially expressed genes involved in amino acid metabolic processes were significantly affected by melatonin. Moreover, the differentially expressed genes associated with stress tolerance, fungicide resistance, and virulence were also affected. These findings contribute to a new understanding of the direct functions of the melatonin on P. infestans and provide a potential ecofriendly biocontrol approach using a melatonin-based paradigm and application to prevent potato late blight.